Report of a Working Group on Sunflower: Fourth meeting, 11-12 May 1991 - International Board for Plant Genetic Resources (1992)
Current activities are reviewed and the following topics of the workplan are considered under the headings: (1) entry of further data into databases; (2) revision of sunflower descriptors; (3) use of a reference line; (4) collecting; (5) rationalization of collections; (6) safety duplication/base collections; (7) future framework for sunflower genetic resources activities in Europe; and (8) an international sunflower genetic resources network. Appendices to the workplan, apart from the list of participants and agenda, cover (1) European database for wild sunflower. 1990 progress report (N. Mihaljcevic); (2) European database for cultivated sunflower: July 1988 to May 1991 (J. Frank and G. Gal); (3) activities on sunflower germplasm preservation (A. Kovacik); (4) sunflower genepool in VIR (V. A. Gavrilova); (5) sunflower genetic resources in Mexico (D. Gomez Sanchez); and (6) IDRC oil crops network for eastern/southern Africa and south/southeast Asia (A. Omran). (Abstract © CAB ABSTRACTS, CAB International)